Mesothelial cyst in the liver round ligament: A case report and review of the literature. (2017) - Feo, Claudio F.; Ginesu, Giorgio C.; Cherchi, Giuseppe; Fancellu, Alessandro; Cossu, M. Laura; Porcu, Alberto
Highlights: Liver round ligament's cysts are rare entities. Due to the low incidence of this pathology the true etiology is unclear. A correct diagnosis is difficult to achieve preoperatively and it is often obtained only after surgical excision. Today, laparoscopy should be regarded as the treatment of choice for mesenteric cysts. Abstract: Introduction: Cysts of the liver round ligament are rare and they are benign in the majority of cases. Current literature has been reviewed on this subject. Presentation of case: A 22-year-old woman with a history of epigastric pain was admitted at our institution. Computed tomography (CT) of the abdomen showed a 14-mm cystic lesion in the epigastrium. A large cyst of the liver round ligament was successfully removed during exploratory laparoscopy and histopathology revealed a benign mesothelial cyst. Discussion: Mesothelial cysts of the liver round ligament are rare entities and we found a total of 5 cases from the literature. Diameter varies from 5 to 14 cm. Most patients were asymptomatic or may complain abdominal pain in the upper quadrants. Ultrasonography and CT scan are the most useful diagnostic tools, however differential diagnosis between various abdominal cystic lesions can be difficult. Treatment is usually surgical excision. Conclusion: Mesothelial cysts of the liver round ligament are extremely rare but should be taken in consideration in the differential diagnosis of intra-abdominal cystic lesions. We stress the importance of exploratory laparoscopy that can allow both diagnosis and radical surgical excision.